Teachers' Emotional Approach Strategy to Students and Its Impact on Learning Effectiveness at MTs Plus Sunan Drajat 7 - M. Fatkul Majid; Atalafairuz Iklil Warsanda; Mustafa Ali Maskur; Irfan Gutawa (Ilmina: Journal of Education and Counseling, 2026)
This study aims to describe teachers’ emotional approach strategies toward students, students’ responses to the emotional approaches applied by teachers, and their impact on the effectiveness of learning at MTs Plus Sunan Drajat 7. This study employs a qualitative approach with a descriptive research design. The research subjects consist of teachers, students, and school officials selected using purposive sampling. Data collection techniques included observation, interviews, and documentation. Data analysis utilized the Miles, Huberman, and Saldana model, which encompasses data reduction, data presentation, and drawing conclusions. Data validity was tested through triangulation of sources, techniques, and time. The research results indicate that teachers’ emotional approach strategies are implemented through warm and open communication, providing attention and empathy to students, offering motivation and positive reinforcement, creating a pleasant learning atmosphere, and adopting an individualized approach toward students facing learning difficulties or personal issues. This strategy received a positive response from students, as evidenced by an increased sense of comfort in learning, higher motivation to learn, improved self-confidence, and active engagement in learning activities. In addition, the teachers’ emotional approach had a significant impact on the effectiveness of learning, namely increased motivation to learn, student participation in the learning process, the creation of a conducive classroom atmosphere, improved learning outcomes, and the development of students’ character and social skills. Thus, the teacher’s emotional approach is one of the effective strategies in supporting the success of learning and the holistic development of students at MTs Plus Sunan Drajat 7.